Quality of Garut ram frozen semen in various glycerol concentrations - Rizal, Muhammad; Toelihere, M.R; Yusuf, T.L; Purwantara, B; Situmorang, P (Indonesian Journal of Animal and Veterinary Sciences, 2002)
Semen was collected once a week using artificial vagina from four mature Garut rams. Immediately after initial evaluation, semen was divided into three parts and diluted with tris extender containing 3% (G3), 5% (G5), and 7% (G7) glycerol, respectively, each with the concentration of 100 million motile sperm 0.25 ml-1. Semen was loaded in 0.25 ml mini straws, and equilibrated at 50C for three hours, then frozen and stored in liquid nitrogen container. Results indicated that percentages of post thawing motility and live sperm for G5 (40 and 50.50%) were significantly higher than G3 (32.50 and 45.33%) (P<0.05), but not significantly different with G7 (39.17 and 47.67%) (P>0.05). Percentages of post thawing intact acrosomal and plasma membrane for G5 (42.67 and 43.17%) were significantly higher than G3 (36.17 and 38.17%) (P<0.05), but not significantly different with G7 (38 and 39.83%) (P>0.05). In conclusion, concentration of 5% glycerol is the optimal dose in maintaining frozen semen quality of Garut rams. Â  Key words: Glycerol concentrations, frozen semen, Garut ram